2017
DOI: 10.3389/fphar.2017.00883
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Case-Finding Algorithm for Identifying Patients with Non-small Cell Lung Cancer (NSCLC) in Administrative Claims Databases

Abstract: Objective: To assess the validity of a treatments- and tests-based Case-Finding Algorithm for identifying patients with non-small cell lung cancer (NSCLC) from claims databases.Data sources: Primary data from the HealthCore Integrated Research Environment (HIRE)-Oncology database and the HealthCore Integrated Research Database (HIRD) were collected between June 1, 2014, and October 31, 2015.Study design: A comparative statistical evaluation using receiver operating characteristic (ROC) curve analysis and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 20 publications
3
25
0
Order By: Relevance
“…This study aimed to examine patient characteristics and treatment patterns among adult patients newly diagnosed with metastatic NSCLC through two RWD sources: health insurance claims data and US nationwide EHRs. 6 (Appendix) Lung cancer drugs included in the study (adapted from Turner et al [13], with inclusion of newly approved drugs and relevant HCPCS codes); (4) with continuous health plan enrollment or active EHR records for at least 6 months before and at least 1 month after the systemic treatment initiation (patients who were deceased within 1 month from systemic treatment initiation were kept in the cohorts); (5) with age ≥ 18 years and known sex at the time of systemic treatment initiation; (6) without any record of receiving SCLC-specific treatments (topotecan, cyclophosphamide, doxorubicin, vincristine, temozolomide, ifosfamide, bendamustine at any time, or platinum + topoisomerase inhibitor combination [cisplatin/carboplatin + etoposide/ irinotecan] as the first-line regimen). Patients were followed from the earliest systemic treatment date until a censoring event (i.e., end of continuous health plan enrollment or active EHR, death, or end of data availability [30 September 2020]).…”
Section: Study Cohortsmentioning
confidence: 99%
“…This study aimed to examine patient characteristics and treatment patterns among adult patients newly diagnosed with metastatic NSCLC through two RWD sources: health insurance claims data and US nationwide EHRs. 6 (Appendix) Lung cancer drugs included in the study (adapted from Turner et al [13], with inclusion of newly approved drugs and relevant HCPCS codes); (4) with continuous health plan enrollment or active EHR records for at least 6 months before and at least 1 month after the systemic treatment initiation (patients who were deceased within 1 month from systemic treatment initiation were kept in the cohorts); (5) with age ≥ 18 years and known sex at the time of systemic treatment initiation; (6) without any record of receiving SCLC-specific treatments (topotecan, cyclophosphamide, doxorubicin, vincristine, temozolomide, ifosfamide, bendamustine at any time, or platinum + topoisomerase inhibitor combination [cisplatin/carboplatin + etoposide/ irinotecan] as the first-line regimen). Patients were followed from the earliest systemic treatment date until a censoring event (i.e., end of continuous health plan enrollment or active EHR, death, or end of data availability [30 September 2020]).…”
Section: Study Cohortsmentioning
confidence: 99%
“…For example, integrated data allow the inclusion of important clinical factors when analyzing health care utilization and costs, as recorded in claims [13]. Such integrated observational data sets have also been used to generate predictive algorithms to better identify patients with cancer [14][15][16][17] and their disease characteristics [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Medical claims data from health insurance systems constitute a potential means for identification of cancer cases, and the performance of this method has been evaluated in several previous studies (4-13). For example, Medicare claims were reported to be accurate in capturing cases of breast, colorectal and endometrial cancer (6,8).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Medicare claims were reported to be accurate in capturing cases of breast, colorectal and endometrial cancer (6,8). The HealthCore Integrated Research Database was found to be sensitive in identifying patients with non-small cell lung cancer (13). For these studies, effective identification of cancer cases can be guaranteed by qualified and accurate diagnostic information in medical claims.…”
Section: Introductionmentioning
confidence: 99%